Negative Grammatical Assumption- descriptive analytical study - Azzam, Nazek Nabeil (Journal of Humanities & Social Sciences, 2020)
The purpose of this study is to shed light on the concept " Negative Grammatical Assumption" descriptive analytical study by explaining it’s meaning, origin, purpose and follow its examples in selected authoresses and analytic it. It’s one of methods that Grammarian use to explain rules of the Arabic syntax. Grammarian intends to mention negative exemplifying phrases with text on abstention of simulation depending on grammar assumption and vision. It stated in spite of its inexistence in Arab talks, formulating it among statements that evoke refusal as in "you shouldn’t say this", "it shouldn’t be permitted", "it’s not good to say", "your saying is offensive"… it aim is imaginative and educational.